The importance of Monte Lussari: A sacrad mountain in the Friuli Alps - Ceruti, María Constanza (2023)
Lussari is a Marian sanctuary located at the eastern end of the Alpine arc, attracting Italian, Austrian, and predominantly Slovenian pilgrims for the past six centuries. Hiking, religious tourism, and pilgrimage exposelocal residents and foreign visitors to a direct experience of the symbolic dimension of the Alpine mountain.This research was based on participant observation during the Pilgrim’s Path, the ascent to the Hunter’s Peaks, and the visit to the sanctuary on the heights of Lussari. It included interviews with visitors, pilgrims, and locals; photographic documentation of ritual settings –summit crosses, chapels, Stations of the Cross, etc.–; readings from the summit book and the book of intentions in the temple; interpretation of ex-votos, offerings, and commemorative plaques; and documentation such as photographic records and field notes. The analysis focused on the symbolic dimension of the high-altitude landscape, considering the conceptual framework provided by Edwin Bernbaum for the study of sacred mountains, as well as that of classical authors in religious anthropology, including Victor Turner and Mircea Eliade, among others. As a result of the investigative work, it is interpreted that the high-altitude sanctuary of Monte Lussari gathers devotees concerned with human fertility, health, and family and social ties traditionally cultivated in this scenic corner of the Julian Alps.